2020
DOI: 10.1073/pnas.2011802117
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing superspreading events and age-specific infectiousness of SARS-CoV-2 transmission in Georgia, USA

Abstract: It is imperative to advance our understanding of heterogeneities in the transmission of SARS-CoV-2 such as age-specific infectiousness and superspreading. To this end, it is important to exploit multiple data streams that are becoming abundantly available during the pandemic. In this paper, we formulate an individual-level spatiotemporal mechanistic framework to integrate individual surveillance data with geolocation data and aggregate mobility data, enabling a more granular understanding of the transmission d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
191
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(221 citation statements)
references
References 23 publications
19
191
1
1
Order By: Relevance
“…First, epidemic outbreaks include stochasticity of multiple kinds. Fluctuations could arise endogenously via process noise (especially at low levels of disease) or exogenously via time-varying parameters, Moreover, given the evidence for clustered transmission and superspreading events ( 18 21 ), extensions of the present model framework should explicitly account for awareness-driven behavior associated with risky gatherings ( 22 , 23 ). Next, the link between severity and behavior change depends on reporting of disease outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…First, epidemic outbreaks include stochasticity of multiple kinds. Fluctuations could arise endogenously via process noise (especially at low levels of disease) or exogenously via time-varying parameters, Moreover, given the evidence for clustered transmission and superspreading events ( 18 21 ), extensions of the present model framework should explicitly account for awareness-driven behavior associated with risky gatherings ( 22 , 23 ). Next, the link between severity and behavior change depends on reporting of disease outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, we judged the use of a negative binomial distribution as a desirable choice, owing to the necessity of counting data [ 15 , 23 , 24 ]. A possible alternative would be the employment of a Poisson distribution, which assumes equal values of mean and variance, making it unusable in the context of COVID-19 due to the well-recognized characteristics of over-dispersion manifested by the spread of this kind of disease, often referred to as a super spreading scheme [ 25 , 26 ]. In conclusion, the opportunity of using a negative binomial distribution is well recognized in the specialized epidemiological literature in the presence of viral spread phenomena, where the distribution of individual infectiousness is often highly skewed much like, for example, in the previous cases of SARS, MERS, and Ebola, in addition to COVID-19 itself.…”
Section: Methodsmentioning
confidence: 99%
“…Based on detailed contact tracing data from Hunan, China, Sun et al [16] found that 15% of cases were responsible for 80% of transmission, and a negative binomial dispersion parameter k of 0.3. Lau et al [17] found that superspreading was widespread across space and time, with an increasing presence towards later stages of the investigated outbreaks, highlighting the importance of maintaining social distance measures. They also found that about 2% of the most infectious cases were directly responsible for 20% of all infections.…”
mentioning
confidence: 91%